PENINGKATAN KETERAMPILAN GURU MA AL-AZIZIYAH PUTERI KAPEK, GUNUNGSARI DALAM MENGEMBANGKAN INSTRUMEN ASESMEN SIKAP DAN KETERAMPILAN HASIL BELAJAR - Dadi Setiadi; Sudirman Wilian; I Nyoman Sridana (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2021)
The purpose of this service is to increase the capability of teachers at MA Al Aziziyah Putri in developing the ability to compose instruments to measure the attitudes and skills of students. The method used in this community service is through training or workshops that are more based on direct practice in compiling instruments that refer to the juridical basis, study of literature, and analysis of teacher needs in the MA Al Aziziyah Puteri environment related to the preparation of attitudes and skills assessment instruments. The implementation of the service is carried out in the following stages: Literature study, analyzing teacher needs, measuring teacher initial abilities, designing training curriculum, training implementation in the form of theoretical studies, practice analysis of skills and attitudes in curriculum documents and preparation of skills and attitude assessment instruments. Monitoring and guidance in the field, Evaluation of Workshop Implementation Results and, Preparation of Service Reports. The population is all female MA Al Aziziyah teachers, the sample used is 40 teachers. The results showed that all participants understood and were skilled in designing instruments for assessing attitudes and skills according to the basic competencies of KD 3 and KD 4 contained in the MA curriculum. However, workshop participants still need training in the preparation of these instruments, especially in determining indicators of attitudes, skills to compiling accurate instruments according to the bill.